2022-RA-1402-ESGO Implementing HRD testing in routine clinical practice among patients with primary high-grade advanced ovarian cancer. (20th October 2022) - Heitz, Florian; Ataseven, Beyhan; Staniczok, Claudia; Denkert, Carsten; Rhiem, Kerstin; Schmutzler, Rita; Heikaus, Sebastian; Moubarak, Malak Moubarak; Welz, Julia; Dagres, Timoleon; Vrentas, Vasilios; Bommert, Mareike; et al.
Abstract : Introduction/Background: Chemotherapy backbone for patients with high-grade advanced epithelial ovarian cancer (HG-AOC) is carboplatin and paclitaxel, followed by a maintenance therapy either with bevacizumab, a PARP inhibitor, or a combination of both which is defined by homologous recombination deficiency (HRD) and BRCA status. Methodology: Inclusion of patients with primary diagnosis of HG-AOC treated in a tertiary gyneco-oncologic center between 12/2019–12/2021. Offering germline testing is recommended by national guidelines and was conducted by using the True-Risk-Panel®. HRD status was measured using the Myriad myChoice® Test in patients with the indication for HRD testing. Results: HRD-testing was requested in 190 patients, and in 163 patients (85.8%) a HRD test result was available. HRD test result could not be reported in 27 patients due to an insufficient tumor yield. Median time to receive the HRD test results was 37 days (range, 8–97). In total HRD was present in 44.7% (73/163) based on GIS ≥ 42 in 42.9% and a tumor BRCA mutation in 3 case (all with GIS<42). Germline testing results were available in 148 patients, and in 18 patients (12.2%) pathological germline mutations were detected. Of the 27 patients without sufficient HRD testing, BRCA germline testing results were available in 19 patients (70.4%), and pathological germline mutations were detected in 2 patients (7.4%). Conclusion: Implementation of HRD testing is feasible and results are available for treatment decisions in a timely manner for most patients. Prerequisite for HRD testing is enough tumor tissue, which should be taken at primary diagnosis of the disease as it is rather unlikely, that enough tumor tissue will be available later after chemotherapy initiation. Co-testing of HRD and BRCA-germline testing should be aimed for to enable optimal, and timely treatment decision on maintenance therapy also for patients in whom the HRD test will not be evaluable.